Development of an improved reverse genetics system for avian metapneumovirus (aMPV): A novel vaccine vector protects against aMPV and infectious bursal disease virus - Lingzhai Meng; Yuntong Chen; Mengmeng Yu; Peng Liu; Xiaole Qi; Xiaoxiao Xue; Ru Guo; Tao Zhang; Mingxue Hu; Wenrui Fan; Ying Wang; Suyan Wang; et al. (Journal of Integrative Agriculture)
Avian metapneumovirus (aMPV), a paramyxovirus, causes acute respiratory diseases in turkeys and swollen head syndrome in chickens. This study established a reverse genetics system for aMPV subtype B LN16-A strain based on T7 RNA polymerase. Full-length cDNA of the LN16-A strain was constructed by assembling 5 cDNA fragments between the T7 promoter and hepatitis delta virus ribozyme. Transfection of this plasmid, along with the supporting plasmids encoding the N, P, M2-1, and L proteins of LN16-A into BSR-T7/5 cells, resulted in the recovery of aMPV subtype B. To identify an effective insertion site, the enhanced green fluorescent protein (EGFP) gene was inserted into different sites of the LN16-A genome to generate recombinant LN16-As. The results showed that the expression levels of EGFP at the site between the G and L genes of LN16-A were significantly higher than those at the other two sites (between the leader and N genes or replacing the SH gene). To verify the availability of the site between G and L for foreign gene expression, the VP2 gene of very virulent infectious bursal disease virus (vvIBDV) was inserted into this site, and recombinant LN16-A (rLN16A-vvVP2) was successfully rescued. Single immunization of specific-pathogen-free chickens with rLN16A-vvVP2 induced high levels of neutralizing antibodies and provided 100% protection against the virulent aMPV subtype B and vvIBDV. Establishing a reverse genetics system here provides an important foundation for understanding aMPV pathogenesis and developing novel vector vaccines.